2014
DOI: 10.1371/journal.pone.0081636
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease Bacteria Specific to Tonsil in IgA Nephropathy Patients Predicts the Remission by the Treatment

Abstract: BackgroundImmunoglobulin (Ig)A nephropathy (IgAN) is the most common form of primary glomerulonephritis in the world. Some bacteria were reported to be the candidate of the antigen or the pathogenesis of IgAN, but systematic analysis of bacterial flora in tonsil with IgAN has not been reported. Moreover, these bacteria specific to IgAN might be candidate for the indicator which can predict the remission of IgAN treated by the combination of tonsillectomy and steroid pulse.Methods and FindingsWe made a comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 66 publications
1
32
1
1
Order By: Relevance
“…The results of this analysis showed that C. rectus or T. denticola may be associated with IgAN [12]. Unfortunately, in the present study, we could not confirm the contribution of T. denticola to IgAN virulence because of the low positive rate of the limited number of saliva specimens.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The results of this analysis showed that C. rectus or T. denticola may be associated with IgAN [12]. Unfortunately, in the present study, we could not confirm the contribution of T. denticola to IgAN virulence because of the low positive rate of the limited number of saliva specimens.…”
Section: Discussioncontrasting
confidence: 63%
“…Recently, we performed an analysis of tonsil flora in IgAN patients, which revealed that the periodontitis-related pathogens Campylobacter rectus and Treponema species were associated with IgAN [12]. We also found that the remission rates of proteinuria and haematuria were significantly related to the prevalence of infection with C. rectus and Treponema species.…”
Section: Introductionmentioning
confidence: 98%
“…Our previous and recent studies regarding the involvement of TLR9 in the pathogenesis of human and murine IgAN indicate that specific antigens are not required for the development of IgAN. However, it seems that there is a biased bacterial flora in tonsil of human IgAN, 41 suggesting that actual exogenous antigens in the pathogenesis may be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Бактерии рода Parvimonas являются условно-патогенными микроорганизмами, играющими роль в развитии агрессивного периодонтита [20]. Aggregatibacter segnis также относится к условно-патогенным микроорганизмам, вызывающим периодонтит [21]. Связь Aggregatibacter segnis с БА установлена впервые, однако из-вестно, что периодонтопатогенные бактерии играют роль в патогенезе ХОБЛ [22], что также показано нами далее.…”
Section: обсуждение основного результата исследованияunclassified